THE MODEL CREATION OF INSTALLATION ART CONTRIBUTED TO THE LOCAL IDENTITY OF BAN NOEN SA-ARD COMMUNITY - Juengprakob, Peerati (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
The model creation of Installation art contributed to the local identity of Ban Noen Sa-Ard Community, it was achieved in cooperation with experienced artists in the field of art design, community leaders and community members. It was under the support and development of teachers’ research potential project, which was organized by the Institute of Research and Development in order to create the model of installation artwork to reflect the local identity of OTOP Tourism Community, Nawat Withi, Ban Noen Sa-Ard , Nakhon Nayok Province "Noen Sa-Ard Model". Phase 1: Direct Observation: it was an observation of the local people in Noen Sa-Ard Community, Moo. 16, Khao Perm Sub-district, Ban Na District, Nakhon Nayok Province by video recording. The primary data were received in this method which was suitable for qualitative research. The methods of observation were as follows: 1) place decoration 2) dress-up for religious ceremonies 3) dialects 4) religious rituals and 5) behaviour of ritual’s participants. The OTOP tourism community project had begun due to the change of the community’s way of life —its’ uniqueness was a goat farm. This project was under the 9101 Project, ‘Following in Father’s Footsteps, Under the Graciousness of His Majesty’ which was philosophy of sufficiency economy and agricultural learning center. Phase 2: Interviewing the Specialists in the field of Installation Art: "Lam-Suk"— the development of installation art according to the specialists’ suggestions regarding local materials or wood scraps, adding some creative ideas to form aesthetic perception and strength for installing in the areas. The data were collected from the community twice in order to have a completed model of installation art. The research results were found that, Neon Sa-ard Community was the OTOP Tourism Community, Nawat Withi— "Neon Sa-Ard Model". The community way of life has been changed from the integrated farming to becoming the agricultural tourism village. This place is currently a tourist attraction where people can learn the philosophy of sufficiency economy — to have balance and sustainable development. The researcher wanted to see the community living and having simple life from the perspective of cultural dimension. The community can present their identity by creating the installation art using the local materials in Ban Noen Sa-Ard Community, Nakhon Nayok Province which this can become a unique environment of the community learning center.